Empowering Wetland Rice Farmers: Strengthening Capability and Income through Farmer Group Participation - Andri Amaliel Managanta; Fiske Angelin Tokare; Toyip; Ita Mowidu (Universitas Muhammadiyah Malang, 2025)
Farmer groups play a role in improving farmers' skills through education, optimizing commodity trade and distribution, and providing agricultural input to increase output. This research aims to determine the various roles of farmer groups and analyze various factors that influence the improvement of farming skills and income of lowland rice farmers. This research was carried out in Buyumpondoli Village, Poso Regency. Buyumpondoli Village was chosen deliberately because it is a rice production center. Sampling was carried out using the proportional random sampling method, with a population of 570 farmers from 21 rice farming groups. By applying the Slovin formula, a sample size of 122 rice farmers was determined. Farmer groups function as learning and production units, helping farmers improve their abilities in cultivation, harvesting, post-harvest, and marketing. However, farmers' farming capabilities are considered moderate and tend to reduce rice farmers' income due to less than an optimal implementation of the cultivation, post-harvest, and marketing processes. Despite this, farmers' income remains high, reaching an average of IDR 5.624.103 per month. Farmer groups should enhance their role as learning platforms by providing regular training and fostering collaboration among members to share knowledge. Additionally, adopting modern agricultural technologies and marketing strategies can help improve productivity and farmers' income.